FEATURES OF HEMODYNAMIC DISORDERS IN PATIENTS WITH TERMINAL GLAUCOMA - E. V. Egorova; O. I. Fabrikantov; S. I. Nikolashin; A. A. Drobnica (Офтальмохирургия, 2015)
Purpose. To study features of different vascular areas of ocular hemodynamics in patients with terminal glaucoma using the ultrasound dopplerography method in a comparative aspect with the fellow eyes without diagnosed glaucoma.Material and methods. The examination was performed in 44 patients: the group 1 (30 eyes) with terminal glaucoma, the group 2 (39 eyes) without diagnosed glaucoma, 25 of these eyes were the fellow (healthy) eyes of patients with primary terminal glaucoma. Standard ophthalmologic examinations were supplemented by the ocular ultrasound dopplerography (USDG), with investigated parameters: Vmax,Vmin,Ri, Pi.Results. Ultrasound dopplerography showed changes in regional blood flow in all investigated parameters (Vmax,Vmin,Ri, Pi) in patients with terminal glaucoma in comparison with the eyes without diagnosed glaucoma. The best preservation of the regional blood flow was identified in the area of the ophthalmic artery in patients with terminal glaucoma, the largest changes in indicators of regional blood flow (Vmax,Vmin,Ri, Pi indexes) were revealed in the area of short posterior ciliary arteries. In four cases (13.3%), blood flow in the short posterior ciliary arteries of the eyes with terminal glaucoma was not determined.Conclusion. In the presence of a general tendency towards a decrease in regional blood flow in patients with terminal glaucoma the ultrasound ocular dopplerography allows to detect the areas of their best maintenance or their damage.